Incidence of Port-Site Hernias: A Survey and Literature Review. Issue 6 (December 2016) - Holihan, Julie L.; Chen, Jeffery S.; Greenberg, James; Hehir, Dermot; Johnston, Sean M.; Marcus, Daniel; Ryan, Heidi; Tsuda, Shawn; Liang, Mike K.
Abstract : Background: The impact of laparoscopy on the prevalence of incisional hernias remains unclear. The aim of this study is to determine (1) surgeon perceptions of port-site hernias (PSHs), (2) the true incidence of PSH. Materials and Methods: A survey on PSH was given to determine the surgeon-reported rate of PSH. A literature review was performed for studies with a primary outcome of PSH. Studies were evaluated using checklists, and scores were used to compare risk of bias. Risk of bias was graphed against PSH incidence. Results: From 38 surgeons surveyed, the surgeon perceived rate of PSH was a median (range) of 0.5% (0% to 5%) for ports ⩽5 mm, 5% (0.1% to 20%) for ports extended, and 5% (0.1% to 40%) for ports ≥10 mm. Thirty studies showed a PSH rate from 0% to 39.3%. Higher quality studies reported higher rates of PSH. Conclusions: Surgeons underestimate the incidence of PSH, but high-quality literature suggests that it may be nearly 40%.